Simultaneous placement of leadless pacemaker and dialysis catheter in patient with exhausted vasculature. Issue 1 (January 2021) - Bednarczyk, Dawid; Kuliczkowski, Wiktor; Letachowicz, Krzysztof; Dzidowski, Marcin; Witkowski, Tomasz; Krajewska, Magdalena; Kusztal, Mariusz; Mysiak, Andrzej; Ściborski, Krzysztof; Mitkowski, Przemysław
The problem with limited venous access may occur in patients receiving long-term hemodialysis treatment with no possibility of arteriovenous access or in patients with cardiac implantable electronic device–related infection leading to the removal of cardiac implantable electronic device. We present a case report where both situations occur simultaneously. Using recent development in cardiac pacing—leadless cardiac pacemaker—we manage to overcome the vascular access problem. The described case emphasizes the necessity of multispecialty collaboration and gains of new pacing technology in patients who need placement of vascular access for hemodialysis and cardiac implantable electronic device where vascular access is scarce.